Mathematician Ignas Saudargas (1902–1987) - Ažubalis, Algirdas (Lietuvos matematikos rinkinys, 2017)
Ignas Saudargas (1902 – 1987) graduated from Vytautas Magnus University in 1932, he studied mathematics. Until the end of World War II worked as a teacher at gymnasiums of Lithuania. He was good teacher, actively participated in  extracurricular activities, always was trying to improve his educational qualifications. After the World War II, he was invited to teach mathematics in universities of Kaunas. I. Saudargas was known for high demands for his students.
Keywords: mathematics; teaching; educational qualification; gymnasium; university